2018
DOI: 10.1186/s13075-017-1501-z
|View full text |Cite
|
Sign up to set email alerts
|

Type I IFN signature in childhood-onset systemic lupus erythematosus: a conspiracy of DNA- and RNA-sensing receptors?

Abstract: BackgroundChildhood-onset systemic lupus erythematosus (cSLE) is an incurable multi-systemic autoimmune disease. Interferon type I (IFN-I) plays a pivotal role in the pathogenesis of SLE. The objective of this study was to assess the prevalence of the IFN-I signature and the contribution of cytosolic nucleic acid receptors to IFN-I activation in a cohort of primarily white cSLE patients.MethodsThe IFN-I score (positive or negative), as a measure of IFN-I activation, was assessed using real-time quantitative PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 32 publications
(39 reference statements)
4
33
2
1
Order By: Relevance
“…Positive blood type-1 IFN gene signatures also occur in substantial numbers of patients with systemic autoimmune disease, including pSS, SLE or SSc. [28][29][30][31] We did not observe a correlation between the disease-specific type-1 IFN gene signature score and serum C1q level in systemic autoimmune disease (pSS, SLE or SLE). Several studies did identify transcriptional differences, as well as similarities, in type-1 IFN-inducible gene signatures between various autoimmune diseases, TB, and normal immune responses, supporting the use of disease-specific IFN gene signatures.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…Positive blood type-1 IFN gene signatures also occur in substantial numbers of patients with systemic autoimmune disease, including pSS, SLE or SSc. [28][29][30][31] We did not observe a correlation between the disease-specific type-1 IFN gene signature score and serum C1q level in systemic autoimmune disease (pSS, SLE or SLE). Several studies did identify transcriptional differences, as well as similarities, in type-1 IFN-inducible gene signatures between various autoimmune diseases, TB, and normal immune responses, supporting the use of disease-specific IFN gene signatures.…”
Section: Discussioncontrasting
confidence: 60%
“…Substantial subsets of patients with pSS, SLE and SSc also display a positive type-1 IFN signature. [28][29][30][31] represents a more general phenomenon, we also determined the relation between serum C1q levels and peripheral blood type-1 IFN signature scores in pSS, SLE and SSc patients. Serum C1q did not show any correlation with the peripheral blood type-1 IFN signature scores in any of these systemic autoimmune diseases (Supplementary figure 1).…”
Section: Inverse Correlation Between Serum C1q Levels and Peripheral mentioning
confidence: 99%
See 2 more Smart Citations
“…[ 59 ] DDX58 gene plays an important role in activating NF-κ B pathway and plays an important role in the pathogenesis of dermatomyositis. [ 60 ] It has been found that DDX58 gene is significantly up regulated in psoriasis patients and psoriasis like mice. [ 61 ]…”
Section: Discussionmentioning
confidence: 99%